2018
DOI: 10.1007/s11356-017-1135-3
|View full text |Cite
|
Sign up to set email alerts
|

Experiment on the treatment of acid mine drainage with optimized biomedical stone particles by response surface methodology

Abstract: The immobilized particles were used to treat acid mine drainage (AMD) in the study, which owns the characteristics of serious pollution and high managing cost. The immobilized particles were prepared with sulfate reducing bacteria (SRB) and medical stones. In order to investigate the interactive influence of medical stones on the particle properties, the salt modification condition, content, and size of the medical stone were taken as the influential factors. At the same time, the removal rate of SO and Mn, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It has been reported that SRB can convert sulfate into sulfide using organic matter under anaerobic conditions [35]. The results of previous studies [36] showed that in the immobilized particles filled with corn cob, SRB and salt-modified Wheat meal stone, the hydrolyzed products of corn cob could be used for SRB growth. When the removal area of SO 4 2is stable, the removal rate of the three kinds of particles has a small difference.…”
Section: Determination Of Corn Cob Particle Sizementioning
confidence: 99%
“…It has been reported that SRB can convert sulfate into sulfide using organic matter under anaerobic conditions [35]. The results of previous studies [36] showed that in the immobilized particles filled with corn cob, SRB and salt-modified Wheat meal stone, the hydrolyzed products of corn cob could be used for SRB growth. When the removal area of SO 4 2is stable, the removal rate of the three kinds of particles has a small difference.…”
Section: Determination Of Corn Cob Particle Sizementioning
confidence: 99%
“…According to the previous research method of Di Junzhen's research group [35][36][37], highactivity SRB immobilized particles were prepared. The production steps of highly active SRB immobilized particles were as follows.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…At the same time, the effluent ORP values of both Column 1 and Column 2 showed a trend of decreasing first and then increasing, and the average ORP values were −63.74 mV and −70.17 mV, respectively. On 1-7 days, the pH value increased rapidly, mainly due to the pH adjustment ability of medical stone [18] and the tight binding of ligands on the surface of bagasse to H 3 O + [11]. The rapid decrease of effluent ORP value at this stage was due to the reaction between AMD and SRB in the particles.…”
Section: Analysis Of the Change Of Ph And Oxidation Reduction Potentimentioning
confidence: 99%
“…It has large surface area, more pores and strong cation exchange capacity, and has been widely used in wastewater treatment [15,16]. In addition, medical stone has a good bidirectional adjustment ability to the pH value in the aqueous solution, and it is capable of adsorbing and fixing metal ions [17,18]. Therefore, if medical stone is used as the filler of microbial immobilized particles, not only the activity of acid pH to SRB can be reduced, but also the metal ions in AMD can be removed by adsorption.…”
Section: Introductionmentioning
confidence: 99%